PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBGAI VARIABEL INTERVENING PADA AYAM GEPREK SA’I DI KOTA PASURUAN - Sri Septiani, Herdiah Eka; Fibriyani, Vita; Wahyuni, Hari (Bhinneka Multidisiplin Journal, 2024)
One of the popular fast food trends is "ayam geprek." One restaurant serving ayam geprek, Ayam Geprek Sa’i in Pasuruan City, has four branches located in various areas of Pasuruan. This study aims to analyse the impact of work motivation on employee performance through job satisfaction as an intervening variable in Pasuruan City. The population used consists of employees of Ayam Geprek Sa’i in Pasuruan City. Employing a saturated sample, the study reached 60 respondents. The data analysis technique used is SEM-PLS. The results show that work motivation significantly affects employee performance at Ayam Geprek Sa’i in Pasuruan, with path coefficients scoring -0.864, a t-statistic score of 5.598, and a significance level of 0.000. Work motivation significantly impacts job satisfaction, with path coefficients scoring 0.966, a t-statistic score of 111.396, and a significance level of 0.000. Job satisfaction significantly affects employee performance, with path coefficients scoring 1.759, a t-statistic score of 12.644, and a significance level of 0.000. This indicates that work motivation and job satisfaction positively impact the improvement of employee performance.